Mekanisme Pemberian Bantuan Hukum Bagi Masyarakat Miskin Di Pengadilan Negeri Samarinda - Jaidun, S.H., M.H (Law Department, University of Widya Gama Mahakam Samarinda, 2015)
ABSTRACT The court is a space or a last fort for people to get justice but in this case a problem which seek the court is not easy and with little expense but rather the cost to be incurred for example using the services of professional lawyers prohibitively expensive while not all people can afford to pay. However, Indonesia as a legal state as mentioned in the Constitution of 1945 in Article 1 point (3)